The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2134/agronj2009.0090
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Breakeven Price of ‘Alamo’ Switchgrass for Biofuels in Tennessee

Abstract: Research on how land suitability affects yields and breakeven prices for switchgrass (Panicum virgatum L.) grown as a bioenergy crop is lacking for the U.S. Southeast. Data from a 3‐yr multilocation experiment at Milan, TN, were analyzed to determine the influence of soil drainage and landscape position on switchgrass yield and farm‐gate breakeven price. Plots were seeded in 2004 with ‘Alamo’ at 2.8, 5.6, 8.4, 11.2, and 14.0 kg ha−1 pure live seed (PLS). Plots were split in 2005 and N was applied at 0, 67, 134… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 24 publications
4
81
2
Order By: Relevance
“…Biomass production on floodplains, however, can be lower than on prime agricultural lands. For example, in a study in the southeastern United States, Alamo switchgrass yielded higher on well-drained upland soils (17.7 Mg ha −1 ) than floodplain soils (8.5 Mg ha −1 ) under different N fertilization rates (0, 67, 134, and 201 kg N ha −1 ; Mooney et al, 2009). The same study found that the maximum switchgrass yields occurred at 67 kg N ha −1 on the well-drained soil and at about 160 kg N ha −1 on the poorly drained floodplain, suggesting that marginal lands can require higher rates of N fertilizer than prime farmlands to produce the same amount of biomass.…”
Section: Flood-prone Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass production on floodplains, however, can be lower than on prime agricultural lands. For example, in a study in the southeastern United States, Alamo switchgrass yielded higher on well-drained upland soils (17.7 Mg ha −1 ) than floodplain soils (8.5 Mg ha −1 ) under different N fertilization rates (0, 67, 134, and 201 kg N ha −1 ; Mooney et al, 2009). The same study found that the maximum switchgrass yields occurred at 67 kg N ha −1 on the well-drained soil and at about 160 kg N ha −1 on the poorly drained floodplain, suggesting that marginal lands can require higher rates of N fertilizer than prime farmlands to produce the same amount of biomass.…”
Section: Flood-prone Soilsmentioning
confidence: 99%
“…The drainage class will influence the energy crop performance. Floodplain soils severely limited by poor drainage (Mooney et al, 2009) can yield less biomass than moderately drained floodprone soils (Evers et al, 2013).…”
Section: Flood-prone Soilsmentioning
confidence: 99%
“…Effects of treatment (stocking rate) on feedstock yield and measures of animal performance (average daily gain and total gain) and economic performance (net return) were analyzed using random-effects mixed ANOVA models using the PROC Mixed procedure in SAS [34,35]. Stocking density treatment (light, moderate, and heavy) was considered as a fixed effect, and year was considered as a random effect.…”
Section: Statisticsmentioning
confidence: 99%
“…According to the 2007 Census of Agriculture, Oklahoma ranks fifth nationally in cattle and calves and fourth in acres in forage, while Texas ranks number one in both of these categories. The Energy Independence and Security Act of 2007 calls for 136 billion liters of biofuels to be produced from renewable resources in the US by 2022 with just under half to be produced from a cellulosic biomass source such as switchgrass [1]. To meet the demand for cellulosic ethanol production called for in The Energy Independence and Security Act of 2007, could require the conversion of acreage currently established in perennial grasses to higher biomass producing grass species such as switchgrass.…”
Section: Introductionmentioning
confidence: 99%